UNRESOLVED CHILDHOOD TRAUMA IN MIKE FLANAGAN’S GERALD’S GAME MOVIE - Nieske Tiara Sabila; Much Khoiri (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This article will analyze Gerald's Game movie, directed by Mike Flanagan. Issues arise regarding the effects or consequences that arise and affect a person's life after experiencing a trauma in childhood and how to deal with unresolved trauma. Jessi, the main female character, is sexually abused as a teenager by her biological father, which traumatizes her into adulthood. The purpose of this article is to analyze how much influence trauma experienced in childhood can affect a person's personal life. This study uses a psychoanalysis approach based on Sigmund Freud's psychoanalytic theory. This article used direct quotations dialogs between characters from Gerald's Game movie. The findings show that the main character's reaction to a traumatic event and how she copes with it, although the event's memory is still attached to her.